Impact of COVID-19 lockdown on the perception of home meals and meal-related variables: A large-scale study within the Italian population during the acute phase of the pandemic. (June 2022) - Piochi, Maria; Buonocore, Federica; Spampani, Francesco; Torri, Luisa
Highlights: Perception of home meals during the lockdown was not uniform among Italians. Older people did not noticeably vary the perception nor the pleasure for home meals. Youngsters appreciated the domestic meals more during the Italian first lockdown. Intense cooking activities, meal dedication and togetherness increased meal pleasure. Meal involvement and cooking-together activities can increase meal appreciation. Abstract: Italy was the first European country struck by the COVID-19 epidemic and experienced a national lockdown. This study explored the effect of lockdown on the perception of any meals prepared and/or conducted at home (home meals) and investigated which variables played a role in this. A group of Italians (n = 3, 060) not suspected/diagnosed as having COVID-19 (18–91 years old; 33% males) completed an online survey during the first lockdown (April 2020). Liking for home meals either increased (51% of the population) or did not vary (43%), while it decreased for only 6% of respondents. Total meal intake similarly either increased (51%) or remained unchanged (33%). Core variables describing meal perception (Liking for meal, Pleasure in meal preparation, Meal duration, Meal Time, Overall food intake, Snack intake) were positively associated with each other. Two clusters with different perceptions of home meals were found, characterised by an increased appreciation (Cl1, 61%) and an unchanged appreciation (Cl2, 39%), respectively. In the acute phase of lockdown, increased meal pleasure was associated with home togetherness (not living alone), cooking with others more often, having high cooking dynamism (use of different kitchen tools, engaging in online food-related activities like using online recipe/website for cooking, use of ready-to-eat meal delivery), and being young, a student or a worker (Cl1). Conversely, Cl2 showed an unchanged meal pleasure, and it was mostly associated with living alone (before and during lockdown), being elderly, retired, widowed, having a low degree of cooking-related activities and dedicating a small weekly budget to food. Variables strictly describing the meal were discussed. Lockdown did not homogenously affect the population in terms of meal pleasure, and high enjoyment of meals was related to high meal involvement. Younger subjects seemed to be more resilient and appreciated meals more due to high cooking dynamism, food-related activities and togetherness. Public health policies could consider these outputs to set up interventions that use meal-dedication activities to increase meal pleasure in vulnerable targets or in subjects experiencing poorly appreciated diets in similar future stressful situations.